Impact of hip abductor and adductor strength on dynamic balance and ankle biomechanics in young elite female basketball players - Domínguez-Navarro, J.; Benitez-Martínez, J. C.; Ricart-Luna, B.; Cotolí-Suárez, P.; Blasco-Igual, J. M.; Casaña-Granell, J. (Scientific Reports, 2022)
This study aimed to evaluate, in an isolated and relative manner, hip abductor (ABD) and adductor (AD) strength and to study the extent to which these factors are related to balance and ankle dorsiflexion mobility in young elite female basketball players. Sixty trainee-level elite female basketball players (13-18 years old), who voluntarily agreed to participate in the study, were divided into three subgroups based on competition age divisions (U14, U16, U18). Isometric hip ABD and AD strength in each leg was evaluated using the ForceFrame Strength Testing System, also calculating the strength ratio and imbalance between legs. Y Balance Test (YBT) and ankle dorsiflexion mobility were also assessed. ANOVA was used for between-group differences analysis. Likewise, the impact of hip strength on balance and ankle mobility was analyzed using Pearson's correlation coefficient. A linear regression model for dependent variables was created with all variables that exhibited significant correlations. A between-group comparison analysis for the three competition age subgroups (U14, U16, U18) revealed non-significant differences (p > 0.005) for the hip strength variables except for hip ABD strength. The correlation study showed low-moderate effect sizes for hip ABD (in both the contralateral and homolateral limb) and AD strength (only the homolateral limb) with YBT and ankle dorsiflexion. However, when performing a regression model, only right hip ABD significantly predicted right limb YBT scores (ß = 0.592, p = 0.048). The present study indicated that, although both hip ABD and AD strength correlate with balance and ankle mobility with low-moderate effect sizes, only hip ABD strength was found to significantly predict YBT scores. Therefore, the potential role of hip ABD strength in particular, but also hip AD strength, for monitoring and enhancing balance and ankle mobility outcomes, should be taken into consideration when designing and implementing preventive strategies for lower-limb injuries.